An upstream uncD sequence modulates translation of Escherichia coli uncC. - Dunn, S D (1990)
The effect of upstream uncD sequences on expression of the Escherichia coli uncC gene, encoding the epsilon subunit of F1-ATPase, was studied. uncC expression was reduced severalfold in plasmid constructs bearing, in addition to uncC, a region of uncD located between 85 and 119 bases upstream from the uncC initiation codon. This reduction was independent of in-frame translation of the uncD sequences. An mRNA stem-loop structure in which sequences located within the inhibitory region of uncD base pair with the uncDC intercistronic region is suggested to function in modulating uncC expression.